Research on Large Scale Antenna Arrays for 5G Mobile Communication Technology - Feng Gao; Kai He; Zhiyuan Song; Wentao Zhu; Lifang Wang; Peng Gao (Dianxin kexue)
The basic conception，background and development of the fifth-generation（5G）mobile communication technology were described. As the key technology of 5G，the research of large scale antenna arrays attracts more and more attention. Thus the basic principle of two-dimensional and three-dimensional array antennas was presented. And on this basis，the tightly coupled phased arrays（TCPA）were introduced. Due to the good properties such as wide in band and small in size，this kind of arrays become a promising candidate for the 5G large scale array antennas. A high-performance 5×5 tightly coupled phased array was designed and simulated.